The Arabic manuscript tradition : a glossary of technical terms and bibliography - Gacek, Adam (Leiden ; Boston : Brill, 2001)
Covering the entire spectrum of Arabic manuscripts, and especially the handwritten book, this book consists of a glossary of technical terms and a bibliography. The technical terms, collected from a variety of sources, embrace a vast range of topics dealing with the studying of Arabic manuscripts.
Acknowledgements; Preface; Part One: GLOSSARY; Part Two: BIBLIOGRAPHY.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
In English and Arabic.
Keywords: Manuscripts, Arabic -- History -- Bibliography; Codicology -- Dictionaries; Arabic language -- Dictionaries -- English; Paleography, Arabic -- Bibliography; Arabic language -- Dictionaries; Manuscrits arabes -- Histoire -- Bibliographie; Codicologie -- Dictionnaires; Arabe (Langue) -- Dictionnaires anglais; Paléographie arabe -- Bibliographie; REFERENCE; Arabic language; Codicology; Manuscripts, Arabic; Paleography, Arabic; Arabische handschriften; Terminologie; Biblioteksvæsen, informations- og kommunikationsvidenskab -- Bog-, tidsskrift- og artikelfortegnelser; Bibliographies; Dictionaries; History